If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-7 + 10x) + 4 = -4 (-7 * -8 + 10x * -8) + 4 = -4 (56 + -80x) + 4 = -4 Reorder the terms: 56 + 4 + -80x = -4 Combine like terms: 56 + 4 = 60 60 + -80x = -4 Solving 60 + -80x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-60' to each side of the equation. 60 + -60 + -80x = -4 + -60 Combine like terms: 60 + -60 = 0 0 + -80x = -4 + -60 -80x = -4 + -60 Combine like terms: -4 + -60 = -64 -80x = -64 Divide each side by '-80'. x = 0.8 Simplifying x = 0.8
| y=6y-10 | | 5y+7=-13 | | 4x+10y-20=0 | | 5m+11=61 | | y=35x-3 | | 3/10x=15 | | 26+m= | | 5/3x-x=x/6-2/3 | | -9r+12=-12 | | 77=18+z | | 6x-7=8x | | 41x=429 | | 3(g-4)=-g | | x-0.05x=10000 | | s+5+9=48 | | 36=y-13 | | 5(x+3.1)=42 | | 14x+2+4x+2=110 | | 3[5-2(x-1)]+2x=-3 | | -27=x^2-16.8x | | 0.6=X/5 | | 10=3/4s | | 7-3n=6n+12 | | t=-0.005x^2+0.45x+125 | | 7+0.2p=5+0.3p | | 4/x-1-2/3x-3=-5/6 | | -4f+2(3f+3)=9 | | (5x+7)(4x-1)= | | -4x-12x-3x=40 | | (6x+7)(4x-1)= | | 3x-12-6x+3=19-3x-1-3x | | 200+6n=500-6m |